The Determination of The Leisure Orientation of University Students And The Investigation of The Purpose of Social Network Uses By Various Variables - Hakan Salim Çağlayan; Nazlı Deniz Öz; Abdil Arı (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to determine  the purpose of using social networking sites for university students . The universe of our search; Seljuk University and the research is composed of 309 students studying in Seljuk University at the different faculties during 2017-2018 education periods.Demographic information form including the questions determined by the researchers and Social Network Sites Usage Scale (8) were used as the data collection tool in the research. In the analysis of the datas, the relevance of normal distribution was tested according to the variables independent t test for binary comparisons and and the non-parametric tests for multiple comparisons without normal distribution relevance Kruskall Wallis test was used. Significance level in the study was taken as 0.05. In conclusion, while there was no difference according to gender, age SASKA variable scale according to the "recognition and for self-promotion" in the lower size 18-20 age group is in favor. According to the class variable, there was a difference between all the other classes in the sub-dimension for “recognition and self-promotion in favor of the 2nd grade. According to the monthly income variable, in the sub-dimension "recognition and self-promotion", significant results were found in favor of 1501 and above income group (p lt;0.05).